MIMO Throughput Effectiveness for Basic MIMO OTA Compliance Testing - Adoración Marín-Soler; Guillermo Ypiña-García; Álvaro Belda-Sanchiz; Antonio M. Martínez-González (International Journal of Antennas and Propagation)
During the March 2011 meeting of the CTIA MIMO OTA Subgroup (MOSG), the members agreed that the subgroup should first determine “what” aspects of a MIMO-capable device require evaluation; then the group should determine “how” to go about making these measurements. In subsequent meetings of MOSG, new yet-unnamed figures of merit were asked for in order to provide a solution to the carriers' requirements for LTE MIMO OTA evaluation. Furthermore, the December 2011 3GPP RAN4 status report on LTE MIMO OTA listed the evaluation of the use of statistical performance analysis in order to minimize test time and help ensure accurate performance assessment as an open issue. This contribution addresses these petitions by providing four new figures of merit, which could serve the purpose of evaluating the operators' top priorities for MIMO OTA compliance testing. The new figures of merit are MIMO Throughput Effectiveness (MTE), MIMO Device Throughput Effectiveness (MDTE), MIMO Throughput Gain (MTG), and MIMO Device Throughput Gain (MDTG). In this paper, MTE is evaluated using the recently available LTE MIMO OTA RR data from 3GPP.